Dekonstruksi terhadap Pemikiran Nur Holis Madjid “Islam Yes, Partai Islam No “: Upaya Menjawab Realitas Partai Islam Indonesia pada Pemilu 2024 - Nata, Yolies Yongky (LITERATUS, 2024)
Deconstruction of Nur Holis Madjid's Thoughts "Islam Yes, Islamic Party No": Efforts to Answer the Reality of the Indonesian Islamic Party in the 2024 Election is an analysis of a Slogan of the Thoughts of the Muslim scholar Nur Holis Madjid which was coined in the 1970s at the Ismail Marzuki mini park in Jakarta its content classifies and criticizes Islam and Islamic Parties. This slogan has shocked the Indonesian world because of the pros and cons of this thought slogan, along with contemporary developments by looking at the existing reality that Islamic parties are now increasingly unable to compete with nationalist parties, so with this approach Concept will be able to analyze Nur Holis Majid's thoughts with the current situation regarding Islamic parties, so that with the Concept approach to Nur Holis Majid's thoughts we can answer why Islamic parties are increasingly lagging behind and by using a conceptual approach we can analyze the relevance of Nur Holis Majid's thoughts on the situation of political parties Contemporary Islam is increasingly not gaining the trust of the Islamic community itself.